Shukor joins YYC as associate partner of tax division - News Straits, Times (New Strait Times, 2017)
KUALA LUMPUR: YYC & Co, a leading local audit and taxation firm, recently announced the appointment of Tan Sri Mohd Shukor Mahfar as associate partner of its tax division, with effect from May 24.